Intrabeam scattering formulas for high energy beams - Kiyoshi Kubo; Sekazi K. Mtingwa; Andrzej Wolski (Physical Review Special Topics. Accelerators and Beams, 2005)
We derive completely integrated formulas for emittance growth times due to intrabeam scattering for charged particle beams in the high energy limit, including the effect of lattice parameters that vary around the accelerator ring. Using accelerator lattices for the prototype damping ring called the Accelerator Test Facility at KEK and those for two proposed International Linear Collider damping rings, we compare our results with other calculations.